2018
DOI: 10.1016/j.cis.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of pattern formation from dried sessile drops

Abstract: The formation of patterns after the evaporation of colloidal droplets deposited on a solid surface is an everyday natural phenomenon. During the past two decades, this topic has gained broader audience due to its numerous applications in biomedicine, nanotechnology, printing, coating, etc. This paper presents a detailed review of the experimental studies related to the formation of various deposition patterns from dried droplets of complex fluids (i.e., nanofluids, polymers). First, this review presents the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
131
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 132 publications
(317 reference statements)
0
131
0
2
Order By: Relevance
“…A general research question to answer is how flow-field in the droplet and other transport phenomena influence the colloidal deposit formed after the evaporation. Various deposit patterns can be observed, as reported in a recent reviews by Larson [9], Sefiane [10] and Parsa et al [11]. A most common example of deposit pattern is the drying of a droplet with particles, such as a coffee spill, which forms a ring-like pattern on the surface.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A general research question to answer is how flow-field in the droplet and other transport phenomena influence the colloidal deposit formed after the evaporation. Various deposit patterns can be observed, as reported in a recent reviews by Larson [9], Sefiane [10] and Parsa et al [11]. A most common example of deposit pattern is the drying of a droplet with particles, such as a coffee spill, which forms a ring-like pattern on the surface.…”
Section: Introductionmentioning
confidence: 82%
“…Droplet evaporation involves two modes, the constant contact radius (CCR) mode, where the contact radius stays constant with the contact angle decreasing, and the constant contact angle (CCA) mode, where the contact angle remains constant with the contact radius decreasing [12] i.e depinning of the contact line. The CCR mode is more likely to happen on hydrophilic substrates while the CCA mode is more usual on hydrophobic substrates [11]. The combination of the two modes generates various particle deposition patterns, as shown in Figure 4.…”
Section: Role Of Contact Line Depinningmentioning
confidence: 99%
“…16 Other research groups have also extensively investigated segregation of binary colloidal particles during drying, both experimentally and numerically. [17][18][19] These fundamental studies contribute to development of a novel method with which a patterned deposition of binary colloidal particles can be obtained by simple drying of binary colloidal suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews by Routh [5] and Parsa et al [6] identified a multitude of parameters, which could play a role in determining the pattern of the final deposit: Marangoni convection, pH of the suspension, particle size, particles shape, particle concentration, substrate temperature, substrate wettability, particles hydrophobicity, relative humidity, electrowetting etc. In particular, Marangoni convection has been shown to reverse the coffee-ring effect [7][8][9][10] and an inner deposit with a much smaller radius than the initial wetted radius is the final outcome instead of the ring.…”
Section: Introductionmentioning
confidence: 99%